Contextual factors and the diffusion of mais in manufacturing and non-manufacturing sectors in Libya - Alhadi Boukr; Hassan Yazdifar; Davood Askarany (Journal of Risk and Financial Management, 2021)
The diffusion of innovation theory has already addressed the major contextual factors hindering or facilitating the diffusion of management accounting innovations (MAIs) in organisations. However, the diffusion of MAIs in less developed countries (such as Libya) is still very low, and the contextual factors addressed by the diffusion of innovation seem to fail to explain the low diffusion. To address this important gap in the literature, this study used contingency theory and investigated the association between a variety of contextual (contingent and institutional) factors and the diffusion of MAIs in Libyan manufacturing and non-manufacturing organisations. Seven MAIs were chosen from the literature perceived to have higher popularity, namely, ABC, ABM, BSC, TC, life-cycle costing, benchmarking, and Kaizen. A questionnaire acted as the data collection instrument. Two hundred and fifty questionnaires were distributed, and one hundred and three useable questionnaires were returned. The results indicate that three factors were significantly associated with facilitating the adoption of MAIs in both sectors. They were using computer systems for MA purposes, top management support, and MA training programmes.
Keywords: 330; management accounting; contextual factors; Emerging Economies; innovations; Libya; manufacturing and non-manufacturing